Peran Zakat Sebagai Solusi Bagi Kesejahteraan Masyarakat Kota Medan - Basri Mahendra Hasibuan; Fadli Darmansyah; Heri Kurniawan; Nurhayati Harahap (Jurnal Penelitian Ekonomi Manajemen dan Bisnis, 2024)
This article tries to summarize the potential of Islamic sharia economics to solve the Indonesian case in the economic aspect. One example is the poverty of society in Indonesia, which is more than half of the population, so this article attempts to discover the economic system in Indonesia, the first country, thereby illustrating the principles of economic value from the perspective of Islamic sharia and internalizing them in the Indonesian economic system. Islam, as the last religion revealed by Allah SWT, has the means of various efforts made to anticipate and resolve the challenges that occur in this era of globalization. The Al-Quran and As-Sunnah as the main sources of Islamic law provide tools so that Islamic teachings are always suitable for all times, namely with Islamic sharia economics being able to solve all economic problems in Indonesia, as stated by As-Shidiqy stating that "In responding to economic problems in At that time, Islamic Economics became a response from Muslim thinkers. In this endeavor, they are guided by the Koran, Sunnah, and use thought and experience as a guide.”